Операційні ризики інфокомунікаційної банківської системи - Стрекозова, Ю. І. (ХНУРЕ, 2019)
The main purpose of managing operational risks of the infocommunication banking system is to ensure their reliability and security. This is due to the desire of banking organizations to meet the needs of customers that arise with the development of their business, in particular, rolling national borders and which require a wide range of banking operations using information systems. The relevance of the research topic is that the regulation of the risk of using information and telecommunication systems is now becoming one of the most important factors ensuring the stability of the banking system.